Effect of Pharmacological Modulation of the Endocannabinoid System on Opiate Withdrawal: A Review of the Preclinical Animal Literature - Wills, Kiri L.; Parker, Linda A. (Frontiers in Pharmacology, 2016)
Over the years, animal studies have revealed a role for the endocannabinoid system in the regulation of multiple aspects of opiate addiction. The current review provides an overview of this literature in regards to opiate withdrawal. The opiate withdrawal syndrome, hypothesized to act as a negative reinforcer in mediating continued drug use, can be characterized by the emergence of spontaneous or precipitated aversive somatic and affective states following the termination of drug use. The behaviors measured to quantify somatic opiate withdrawal and the paradigms employed to assess affective opiate withdrawal (eg. conditioned place aversion) in both acutely and chronically dependent animals are discussed in relation to the ability of the endocannabinoid system to modulate these behaviors. Additionally, the brain regions mediating somatic and affective opiate withdrawal are elucidated with respect to their modulation by the endocannabinoid system. Ultimately, a review of these findings reveals dissociations between the brain regions mediating somatic and affective opiate withdrawal, and the ability of CB1 receptor agonism/antagonism to interfere with opiate withdrawal within different brain sub regions.